Potential Treat-to-Target Approach for Methamphetamine Use Disorder: A Pilot Study of Adenosine 2A Receptor Antagonist With Positron Emission Tomography - Okita, Kyoji; Matsumoto, Toshihiko; Funada, Daisuke; Murakami, Maki; Kato, Koichi; Shigemoto, Yoko; Sato, Noriko; Matsuda, Hiroshi (Frontiers in Pharmacology, 2022)
Introduction: The misuse of stimulant drugs such as methamphetamine is a global public health issue. One important neurochemical mechanism of methamphetamine use disorder may be altered dopaminergic neurotransmission. For instance, previous studies using positron emission tomography (PET) have consistently shown that striatal dopamine D2-type receptor availability (quantified as binding potential; BPND) is lower in methamphetamine use disorder. Further, methamphetamine use is known to induce chronic neuroinflammation through multiple physiological pathways. Upregulation of D2-type receptor and/or attenuation of neuroinflammation may therefore provide a therapeutic effect for this disorder. In vitro studies have shown that blockage of adenosine 2A (A2A) receptors may prevent D2-receptor downregulation and neuroinflammation-related brain damage. However, no study has examined this hypothesis yet. Methods and Analysis: Using a within-subject design, this trial will assess the effect of the selective A2A receptor antagonist, istradefylline, primarily on D2-type BPND in the striatum, and secondarily on neuroinflammation in the whole brain in individuals with methamphetamine use disorder. The research hypotheses are that istradefylline will increase striatal D2-type BPND and attenuate neuroinflammation. Twenty participants with methamphetamine use disorder, aged 20–65, will be recruited to undergo [11C]raclopride PET (for every participant) and [11C]DAA1106 PET (if applicable) once before and once after administration of 40 mg/day istradefylline for 2 weeks. Neuropsychological measurements will be performed on the same days of the PET scans.